Bride for rent - Chiu, Kim.; Lim, Xian.; Marquez, Empoy; Star Cinema (Quezon City Star Cinema, 2014)
A young man trying to get at his inheritance hires a woman to play his bride. But though it's just supposed to be an act, things get unexpectedly real between them.--imdb.com.
Charlene Grace Bernardo, story and screenplay; Mae Czarina Cruz, director.
Kim Chiu, Xian Lim, Empoy Marquez.
DVD.
Keywords: Romantic comedy films; Feature films